Reliable robust path planning with application to mobile robots - Pepy, Romain; Kieffer, Michel; Walter, Eric (Zielona Góra: Uniwersytet Zielonogórski)
This paper is devoted to path planning when the safety of the system considered has to be guaranteed in the presence of bounded uncertainty affecting its model. A new path planner addresses this problem by combining Rapidly-exploring Random Trees (RRT) and a set representation of uncertain states. An idealized algorithm is presented first, before a description of one of its possible implementations, where compact sets are wrapped into boxes. The resulting path planner is then used for nonholonomic path planning in robotics.
Keywords: interval analysis; path planning; robust control; state-space models